Catatonia in inpatients with psychiatric disorders: A comparison of schizophrenia and mood disorders. Issue 3 (30th October 2015) - Grover, Sandeep; Chakrabarti, Subho; Ghormode, Deepak; Agarwal, Munish; Sharma, Akhilesh; Avasthi, Ajit
Abstract: This study aimed to evaluate the symptom threshold for making the diagnosis of catatonia. Further the objectives were to (1) to study the factor solution of Bush Francis Catatonia Rating Scale (BFCRS); (2) To compare the prevalence and symptom profile of catatonia in patients with psychotic and mood disorders among patients admitted to the psychiatry inpatient of a general hospital psychiatric unit. 201 patients were screened for presence of catatonia by using BFCRS. By using cluster analysis, discriminant analysis, ROC curve, sensitivity and specificity analysis, data suggested that a threshold of 3 symptoms was able to correctly categorize 89.4% of patients with catatonia and 100% of patients without catatonia. Prevalence of catatonia was 9.45%. There was no difference in the prevalence rate and symptom profile of catatonia between those with schizophrenia and mood disorders (i.e., unipolar depression and bipolar affective disorder). Factor analysis of the data yielded 2 factor solutions, i.e., retarded and excited catatonia. To conclude this study suggests that presence of 3 symptoms for making the diagnosis of catatonia can correctly distinguish patients with and without catatonia. This is compatible with the recommendations of DSM-5. Prevalence of catatonia is almost equal in patients with schizophrenia and mood disorders. Highlights: Threshold of 3 symptoms correctly categorize 89.4% of patients with catatonia. Threshold of 3 symptoms correctly categorize 100% patients without catatonia. Prevalence of catatonia in our study sample was 9.45%. No difference in the prevalence rate of catatonia between schizophrenia and mood disorders. Factor analysis of the data yielded 2 factor solutions, i.e., retarded and excited catatonia. Findings of the study are consistent with the DSM-5 definition of catatonia.